Comparison of selected tools to perform unit tests - Strzelecki, Piotr; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2018)
The paper presents a comparative analysis of selected tools to perform unit tests. The analysis covers three most popular frameworks: MSTest, NUnit and xUnit.net. The analysis concerns the comparison of the speed of tests performing by the tools in serial and parallel manner. The tests were carried out by the author’s application dedicated to .NET platform.